The calcium and phosphate L values of a soil as affected by test crop and calcium phosphate form - Harry, Raymond Brydon Albert (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1967.